«Muchas veces hemos tratado por cartas familiarmente»: Gonzalo Pérez y Juan Páez de Castro, historia de una colaboración - Juan Ramón Muñoz Sánchez (E-Spania, 2023)
In the present work we intend to outline the history of the relationship of Gonzalo Pérez and Juan Páez de Castro, both of the protection that the Secretary of State gave to the humanist as well as of the collaboration of the latter with the former in the translation of the Odyssey.